Filsafat Pendidikan Islam Sunni-Madura (Studi Konsep Pendidikan Islam Masyarakat Sunni-Madura) - Achmad Bahrur Rozi; Misnatun Misnatun (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2020)
The ideal relationship between education and theology should be functional-mutualism so that education has a strong spirit and foundation. As well, theology can have practical and contributory meaning in social life. So education is not just an effort to producing